Islamic Review of Impulsive Buying on Shopee for UNIDA Gontor Students 2022 - Amin Fonda Astiti Rob Rahayu; Nusa Dewa Harsoyo; Ahmad Suminto (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
Based data of administration Gontor for girls first campus, there are 49,08 % of the total female students receiving packages from shopee. In fact, the campus has provided facilities in the form of a mini market. However, there are still many students who like to shop online. The purpose of this research is to analyze impulsive buying behavior judging from islamic perspective. This study uses a descriptive qualitative method using primary and secondary data. The data collection techniques used triangulation, which were carried out on 10 informants and also 111 respondents using shopee who made purchases at least 1 time in 1 month. The results of this study are that the category of impulsive buying among female students at University of Darussalam Gontor in 2022 is mostly in the suggested and planned impulsive buying categories, but sometimes there are also reminders of impulsive buying. The students have implemented consumption behavior that is in accordance with Islamic teachings. For future researchers, it is expected to add other variables that may not have been examined by the author in order to find out other variables that have a major influence on impulsive buying behavior on the Shopee online site. Keywords: Impulsive Buying, Shopee, Islamic Review